3D Visualization of Molecules from Structural Formulas: An Interactive Approach - Amorim, Eduardo; Valdo, Ana; Soares, Fabrizzio; Felix, Juliana; Cardoso, Luciana; Aranha, Renan Vinicius; Nascimento, Thamer Horbylon (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2024)
This work presents the development of a system whose main objective is to convert two-dimensional (2D) representations of chemical molecules into interactive three-dimensional (3D) models. The aim is to enhance the understanding of molecular structures through a more intuitive and dynamic visualization. The system allows users to either capture a photo of a hand-drawn 2D molecule or draw a molecule directly on the screen of a mobile device. The input image is processed to generate a 3D model that can be manipulated and examined from different angles, facilitating the analysis of molecular geometries. This approach not only bridges the gap between traditional 2D chemical diagrams and modern 3D visualization but also provides a valuable educational tool for chemistry students and professionals. Our ongoing work aims to further improve the user interface and enhance the accuracy of 3D rendering to support a broader range of molecular structures.